Hope in the uncertainties and certainty for parents of children with rare neurological disorders. Part I (of 3): Uncertainty. (7th September 2022) - Palmer, Elizabeth E; Sachdev, Rani; Beavis, Erin; Macintosh, Rebecca; Le Marne, Fleur A; Nevin, Suzanne M; Bye, Ann ME; Nunn, Kenneth
Abstract : This is the first of three articles exploring the aspects of clinical care for children with rare neurological disorders including uncertainties old and new. The disruptive technologies of genomic sequencing and advanced therapeutics such as gene‐based therapies offer parents of children with severe but rare neurological conditions for the first‐time unprecedented opportunities for 'precision medicine'. At the same time, the realities of limited genomic diagnostic yields and not infrequent detection of variants of uncertain significance, lack of natural history study data and management guidelines for individually rare neurogenetic conditions, means that high pre‐genomic test expectations are all too often replaced by an accumulation of new uncertainties. This can add to the chronic traumatic stress experienced by many families but may also have under‐recognised impacts for their clinicians, contributing to 'burn‐out' and attendant negative psychosocial impacts. This first article aims to address how clinicians might manage the accumulation of uncertainties to be more helpful to patients and their families. Moreover, it seeks to address how clinicians can move forward providing compassionate care to their patients and a little more consideration for themselves.